Pengaruh Metode Blended Learning dalam Penerapannya dan Sisi Negatif Penggunaan Jangka Panjang - Feni Melina Suandari; Rizky Suganda Putra; Via Erista Nurjanah (Program Studi PGSD Kampus UPI di Serang, 2021)
The blended learning method is basically a combination of the advantages of faceto-face and virtual learning. The blended learning method is a simple learning method that combines various delivery methods, teaching models and learning styles. Blended learning can give students the flexibility to freely choose when and where to access teaching materials. This study aims to analyze the effectiveness and influence of blended learning methods in the future. The method used is a systematic review of the literature. The results of the compilation of several articles on blended learning at the education level, the researchers reduced the articles so that the literature review was in accordance with the topics contained in this article. Based on the research results obtained, to increase student effectiveness there are several supporting elements such as face-to-face, independent learning, online media, tutorial materials, collaboration, smooth internet connection, capable devices, and evaluating learning. With some of these elements can create effectiveness in blended learning learning methods.